Femtosecond laser scribing of Mo thin film on flexible substrate using axicon focused beam. (October 2015) - Yu, Xiaoming; Ma, Jianfeng; Lei, Shuting
Abstract: Ablation experiments of molybdenum (Mo) thin film on flexible polyimide (PI) substrate are conducted using femtosecond laser pulses focused by an axicon lens. The purpose is to assess the capability of axicon lens in producing narrow grooves and how robustness the scribing process is. We first obtain the damage threshold of Mo and PI and then characterize the spatial beam profile produced by the axicon lens through both theoretical calculations and experimental measurements. Then scribing experiments are performed with different pulse energy, scanning speed, and the distance between the axicon tip and the sample's surface. Optical microscope and atomic force microscope are used to examine the microgrooves from the experiments. It is shown that high quality narrow scribes can be produced with axicon focused beam which can tolerate large height fluctuations of moving flexible substrate expected in an industrial setting.